Periodismo informativo guayaquileño en plataformas streaming - Vélez Albán, Byron Walther (2019)
Informative journalism in recent years has been modified with the arrival of the digital age, new elements and platforms for communication have been announced, currently the information has been used is different, users have accessed it easily and instantly through electronic devices with an internet connection. The media have had the arduous task of adapting to this new consumer trend that is advancing by leaps and bounds, using various digital platforms for the consumption of information. For this research, streaming platforms were taken, because they have taken great value over the years, for the construction of new informative journalistic proposals……….